Urban Encounters: Climate Art and the Public - Mei-Hsin Chen (Calle 14: Revista de Investigación en el Campo del Arte)
This article examines the importance of public spaces as conduits for communication and education and platforms for spreading awareness of global warming through artistic expression. It explores how these spaces function, the impact of artworks in urban environments, and the role of public art in addressing sustainability issues. By categorizing public spaces into social and quotidian realms, the article highlights their potential as forums for discussion and learning about global issues. The article uses case studies, such as the projects of Daan Roosegaarde and Eve Mosher, to illustrate how climate art engages viewers in contemplating a more sustainable future through emotional and sensory experiences.